Upaya Kaum Nahdliyyin untuk Melestarikan Tradisi Lokal dalam Kegiatan Keagamaan di Indonesia - Abdullah, A. Fatikhul Amin; Iskandar, Mohammad; Rahman, Muhammad Hadiatur (IJTIMAIYA: Journal of Social Science and Teaching, 2024)
This research is motivated by this collision occurs between fellow Muslims in Indonesia to live a religious life often occur because of differences in the implementation of religious activities in cultural traditions. This study describes the relationship between religion and local traditions as well as the need to maintain local traditions in religious practices as well as the efforts made to preserve local traditions NU. For that the method used is the historical research methods and methods for collecting data to study the documents, literature study, observation, and interviews NU figures. This Study uses structuration theory Anthony Giddens about Agents, Agency, Structure, and Duality of Structure. NU declared himself as the successor of propaganda struggle Walisongo were also very tolerant of local traditions that make efforts to maintain its religious rituals without removing the existing local traditions.